Testing the Motor Simulation Account of Source Errors for Actions in Recall - Lange, Nicholas; Hollins, Timothy J.; Bach, Patric (Frontiers in Psychology, 2017)
Observing someone else perform an action can lead to false memories of self-performance - the observation inflation effect. One explanation is that action simulation via mirror neuron activation during action observation is responsible for observation inflation by enriching memories of observed actions with motor representations. In three experiments we investigated this account of source memory failures, using a novel paradigm that minimized influences of verbalization and prior object knowledge. Participants worked in pairs to take turns acting out geometric shapes and letters. The next day, participants were recalled either actions they had performed or those they had observed. Experiment 1 showed that participants falsely retrieved observed actions as self-performed, but also retrieved self-performed actions as observed. Experiment 2 showed that preventing participants from encoding observed actions motorically by taxing their motor system with a concurrent motor task did not lead to the predicted decrease in false claims of self-performance. Indeed, Experiment 3 showed that this was the case even if participants were asked to carefully monitor their recall. Because our data provide no evidence for a motor activation account, we also discussed our results in light of a source monitoring account.